Studi Komparatif Kinerja Reksadana Saham Konvensional dan Syariah Di Indonesia - Faizal Ridwan Zamzany; Edi Setiawan (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This study aims to compare the performance of conventional stock mutual funds and Islamic stock mutual funds with the Sharpe Index method, Treynor Index, and Jensen Index. This study aims to determine whether there are differences in performance between conventional mutual funds and Islamic mutual funds. The population in this study is mutual funds managed by Investment Managers who manage both subcategories of conventional and sharia mutual fund types of shares. This type of research is comparative research. The data used are secondary data obtained from published reports by the Financial Services Authority (OJK). The results of the study using Sharpe, Treynor and Jensen methods show that the performance of conventional and Islamic equity funds has a performance above risk-free investment performance. With these three results, the performance of conventional and Islamic stock mutual funds does not have a significant difference.